Pemasangan Hole Guard Rail pada UPT. Pengujian Kendaraan Bermotor Dinas Pekerjaan Umum, Tata Ruang, Perhubungan dan Pertanahan Kabupaten Maros - Adrianus Surianto Girikallo (Lembaga Pengembangan Kinerja Dosen, 2024)
Community service activities (PKM) are an integral part of the Tri Dharma, namely Teaching, Research and Community Service. This PKM activity is carried out by Lecturers routinely every semester which aims to contribute to the community in the application of knowledge needed to face very dynamic developments and changes in all aspects of life. The synergy and collaboration of academics and the community are expected to have a positive impact on both society and the University. Community service activities are inseparable from the other Two Dharmas, and involve all Academics, namely lecturers, students, education staff and alumni. Through PKM, the academic community can be present in the midst of society in order to help with various problems faced by the community. The community service activity (PKM) carried out in the even semester of the 2023/2024 academic year was the installation of a hole guard rail (Hole Guard Rail) for inspection or inspection of the lower part of the Test Vehicle which is often referred to as the Undercarriage of Vehicles. The motor vehicle test hole or tunnel is one of the facilities at the Motor Vehicle Testing UPT (PKB). The purpose of installing this Safety Rail is to implement Safety First, namely preventing cars or test vehicles from falling into holes or test tunnels and ensuring that services to the public using the service can run smoothly as expected. The construction of this Safety Rail uses two types of UNP profile steel (U channel), namely U channel 100 and 50. U channel 100 is for the safety rail or barrier while channel 50 is for the support pole or support for the Safety Rail. This steel construction is glued or tied with an Electric arc welding system (SMAW). The total cost of this construction is borne by the Head of UPT PKB, Maros Regency.